Aborsi pada Perimenopause Korban Pemerkosaan Perspektif Hukum Positif dan HAM - Ulva, Farida; Akmal, Muhamad; Ningsih, Siti Fauziah; Putri, Nandita Sagarmatna Darmayanti; Alhafiz, Muhammad (Al Muhkam: Journal of Islamic Law and Jurisprudence, 2025)
Cases of rape against perimenopausal women in Indonesia often created ethical and legal dilemmas concerning abortion, in which the right to life of the fetus conflicted with the victim’s rights to physical and mental health, as well as human dignity. This study examined the regulation of abortion under positive law (Articles 346–349 of the Criminal Code and Article 60 paragraph (2) of Law No. 17 of 2023) and analyzed it from a human rights perspective in balancing these competing rights, particularly in relation to elderly victims who were vulnerable to prolonged psychological trauma. The study employed a qualitative normative approach based on library research. Research data were derived from statutes, academic journals, and legal literature, and were analyzed using a descriptive-analytical method. The findings indicated that abortion was legally permitted in cases of rape with medical indications. However, the study emphasized that priority should be given to the health of perimenopausal victims, considering the high risks associated with pregnancy at that age. The analysis highlighted the importance of restorative justice, legal protection for medical professionals, and efforts to reduce social stigma. The study recommended regulatory revisions to ensure more responsive access to abortion services that took individual circumstances into account, in order to realize a just human rights framework.